2012
DOI: 10.4049/jimmunol.1103152
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 and IL-7 Determine the Homeostatic Balance between the Regulatory and Conventional CD4+ T Cell Compartments during Peripheral T Cell Reconstitution

Abstract: Work over the last decades has led to the identification of the factors that influence the survival and homeostasis of conventional T cells. IL-7 and TCR signaling promote the survival of naive CD4+ and CD8+ T cells in lymphoreplete mice and their proliferation in a lymphopenic environment, whereas survival and homeostatic proliferation of memory CD4+ and CD8+ T cells crucially depend on a combination of IL-7 and IL-15. In contrast, there is little information regarding the factors driving the proliferation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 58 publications
1
23
1
1
Order By: Relevance
“…This result seems contradictory to the work from Ribot et al (13) studies describing g/d T cell memory-type responses in mice after Staphylococcus aureus infection (35), in macaques following a secondary challenge with bacillus Calmette-Guerin (36), or in humans in a CMV infection context (37). When transferred into a lymphopenic environment, naive a/b T cells proliferate strongly and acquire a memory-like phenotype (20,27,38). In our study, we observed that naive-like Ly-6C 2 and Ly-6C + CD44 lo g/d T cell subsets were able to undergo lymphopenia-induced spontaneous proliferation and to convert to a memory-like phenotype (Ly-6C + CD44 hi ) while increasing their capacity to produce IFN-g, suggesting that these three g/d T cell subsets would actually correspond to various differentiation stages of a unique T cell lineage.…”
Section: Cd44contrasting
confidence: 55%
See 1 more Smart Citation
“…This result seems contradictory to the work from Ribot et al (13) studies describing g/d T cell memory-type responses in mice after Staphylococcus aureus infection (35), in macaques following a secondary challenge with bacillus Calmette-Guerin (36), or in humans in a CMV infection context (37). When transferred into a lymphopenic environment, naive a/b T cells proliferate strongly and acquire a memory-like phenotype (20,27,38). In our study, we observed that naive-like Ly-6C 2 and Ly-6C + CD44 lo g/d T cell subsets were able to undergo lymphopenia-induced spontaneous proliferation and to convert to a memory-like phenotype (Ly-6C + CD44 hi ) while increasing their capacity to produce IFN-g, suggesting that these three g/d T cell subsets would actually correspond to various differentiation stages of a unique T cell lineage.…”
Section: Cd44contrasting
confidence: 55%
“…Surface staining was performed as previously described (20,21). Briefly, cells were incubated on ice, for 15 min per step, with Abs in 5% FCS (Biochrom) and 0.1% NaN 3 (Sigma-Aldrich) PBS.…”
Section: Fluorescence Staining and Flow Cytometrymentioning
confidence: 99%
“…Therefore, increased availability of IL-7 may enhance peripheral expansion in response to both high-affinity and low-affinity antigens [8] and may promote alloreactivity to low-affinity minor antigens and thereby progression to aGVHD. In addition, elevated IL-7 levels may cause a functional shift within the T cell compartment, as IL-7 has minimal impact on the homoeostatic proliferation of regulatory T cells (Tregs) [33,43] that are thought to inhibit the development of aGVHD and found at reduced levels in patients with aGVHD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…62 This observation has led to low-dose IL-2 as therapy to promote Treg proliferation in hepatitis C-associated vasculitis 63 and GVHD following stem cell transplantation. 64 IL-2 therapy for GVHD restores pStat5 signaling and proliferation of T regs without affecting T convs .…”
Section: Clinical Implications For Autoimmunity After Treatment Omentioning
confidence: 99%